2020
DOI: 10.1021/acs.chemrestox.0c00028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atomizer Age and Flavor on In Vitro Toxicity of Aerosols from a Third-Generation Electronic Cigarette against Human Oral Cells

Abstract: Electronic cigarettes (ECs) are categorized into generations which differ in terms of design, aerosol production, and customizability. Current and former smokers prefer third-generation devices that satisfy tobacco cravings more effectively than older generations. Recent studies indicate that EC aerosols from firstand second-generation devices contain reactive carbonyls and free radicals and can cause in vitro cytotoxicity. Third-generation ECs have not been adequately studied. Further, previous studies have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 45 publications
6
29
0
Order By: Relevance
“…20,21 Seven studies were conducted in the US, 5,6,20,[22][23][24] two in Canada, 21,25 two in Switzerland, 26,27 three in Germany, [28][29][30] two in Italy, 31,32 one in Poland, 33 and one in Brazil. 34 Four studies examined e-cigarette liquid on oral cells, 28,29,[31][32][33]35,36 nine e-cigarette vapor, 5,6,[20][21][22][25][26][27]37 four tested cigarette liquid and vapor, 6,33,37,38 and one study the effects of vapor on DNA. 34 Nicotine concentration ranged from 0 to 24 mg/ml, and 12 flavors were tested for toxicity.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…20,21 Seven studies were conducted in the US, 5,6,20,[22][23][24] two in Canada, 21,25 two in Switzerland, 26,27 three in Germany, [28][29][30] two in Italy, 31,32 one in Poland, 33 and one in Brazil. 34 Four studies examined e-cigarette liquid on oral cells, 28,29,[31][32][33]35,36 nine e-cigarette vapor, 5,6,[20][21][22][25][26][27]37 four tested cigarette liquid and vapor, 6,33,37,38 and one study the effects of vapor on DNA. 34 Nicotine concentration ranged from 0 to 24 mg/ml, and 12 flavors were tested for toxicity.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…29 Another study used oral keratinocytes, 36 and 2 studies used premalignant keratinocytes, laryngeal lymph cells, and head and neck squamous epithelial cells. 6,23 Eight studies used donor tissue to create cell lines, [26][27][28][29][32][33][34]38 8 studies used cultured cell lines, 5,6,20,21,32,35,37,39 and 2 studies used research participants 20,36 (See Table 3).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that vaping can be a reason for relapse into traditional smoking [3]. Moreover, it was found that third-generation electronic cigarettes may cause adverse effects in the oral cavity, and normal e-cigarette use, which involves repeated use of the same atomizer to generate aerosol, may enhance the potential toxic effects of third-generation e-cigarettes [4].…”
Section: Introductionmentioning
confidence: 99%